Reflections on Pedagogical Practices for Online Teaching. (4th March 2021) - Chetty, Rajendra
Abstract: This article is a reflection on my online teaching at the advent of the COVID-19 pandemic. The aim is to provide strategies to integrate transformative pedagogical practices with online teaching platforms. The methodological framework for the article is reflective practice. I reflect on my online teaching of an English language module, pay critical attention to the practical values that inform self-directed learning, engage with student reflections on challenges experienced during the lockdown, and aim for developmental insight. The article advocates for self-directed learning and engagement with pedagogical foundations of e-learning to counter the common technical perspective to online teaching. Uploading course material and limiting facilitation to giving directions on assignments and providing technical resources is inadequate. The imperative is critical engagement with knowledge underpinned by self-directed learning within social and emancipatory frameworks. Traditional student dependence on lectures should shift to them assuming responsibility for the cognitive (self-monitoring) and contextual (self-management) process of learning. The article calls for vigorous dialogue to counter feelings of depersonalisation and isolation, intense intellectual relationships, transformative pedagogies, innovative thinking around teaching time, and organisation and advanced communication skills for online classrooms. The student, the nature of learning, learning strategies, phases of the learning process, and the knowledge project should be taken into account in mapping the process of self-directed learning.